Using music as a mood regulator in everyday life is associated with unfavourable health and fitness outcomes in overweight adults - Laura Ginström; Kaisa Kaseva; Juha E. Peltonen; Suvi Saarikallio; Mari Tervaniemi (PLoS ONE, 2025)
Individual traits and habits have shown to be associated with health and health behaviour. One such habit is how individuals use music. This study aimed to examine if using music as a mood regulator is related to risk factors of lifestyle diseases. Participants who joined the present Motivation Makes the Move! lifestyle intervention were overweight and sedentary adults (n = 76, ages 19–40). They answered questionnaires about physical activity and use of music. They also underwent a cardiopulmonary exercise test and their body composition was assessed. Additionally, the analyses’ robustness was tested through controlling for physical, sociodemographic and psychological health related factors. We observed that despite the participants’ self-reported commitment to regular physical activity, their fitness level was poor. Using music as a mood regulator was associated with lower cardiorespiratory fitness. Use of music was also positively linked to body fat percentage, although this finding did not remain significant after adjusting for age, educational level and experienced health. We urge future research to address the relationship between music use and risk factors of lifestyle diseases in a population sample.